China’s urban agglomerations as drivers of synergistic pollution and carbon reduction - Wang, Ruxiao; Feng, Fengcun; Khalid, Zainab; Nisar, Ubair (Frontiers in Environmental Science, 2025)
IntroductionThis study investigates the impact of China’s national-level city cluster policy on the synergistic governance of urban pollution reduction and carbon reduction, focusing on both “quantity reduction” (PM2.5 and CO2 emissions) and “efficiency improvement” (governance effectiveness). The research explores how the policy, as a quasi-natural experiment, contributes to these dual objectives.MethodsUsing panel data from 274 prefecture-level and above cities from 2006 to 2023, the study employs a difference-in-differences (DID) model to estimate the impacts of the policy. Additionally, mediating and moderating effect analyses are incorporated to explore the mechanisms driving the outcomes.ResultsThe findings reveal that the city cluster policy significantly reduces PM2.5 concentrations and CO2 emissions in pilot cities, while simultaneously enhancing governance efficiency. Mechanism analysis identifies three main drivers: green technology innovation, knowledge spillovers, and industrial structure upgrading. Heterogeneity tests show that the quantitative effects (e.g., pollution reduction) are stronger in hub cities, while efficiency gains are more pronounced in non-resource-based cities. There are no significant differences between hub and non-hub cities for efficiency, and no significant impact of resource endowment on quantity reduction.DiscussionThis study contributes to the literature in three key ways: (1) it develops a dual-dimensional framework to assess both “quantity reduction” and “efficiency improvement” in pollution and carbon governance; (2) it uncovers the mechanisms through which the city cluster policy operates; and (3) it identifies regional heterogeneity in the policy’s effects across different types of cities. The findings underscore the dual benefits of the policy, validate the mediating mechanisms, and highlight the role of regional differences in the outcomes. Policy implications include expanding and institutionalizing the pilot programme, fostering green innovation, and tailoring city cluster development strategies to local conditions.